Enantiomeric separation of 1-phenyl-1-propanol using calix [4]arene-capped β-cyclodextrin-bonded silica particles as chiral stationary phase in capillary electrochromatography - Zhao, J. (2014)
10.4028/www.scientific.net/AMR.749.304